Deep Dyspareunia: Review of Pathophysiology and Proposed Future Research Priorities. (28th March 2019) - Orr, Natasha; Wahl, Kate; Joannou, Angela; Hartmann, Dee; Valle, Lisa; Yong, Paul; ,; Babb, Corey; Kramer, Catherine W.; Kellogg-Spadt, Susan; Renzelli-Cain, Roberta I.
ABSTRACT: Introduction: Dyspareunia has been traditionally divided into superficial (introital) dyspareunia and deep dyspareunia (pain with deep penetration). While deep dyspareunia can coexist with a variety of conditions, recent work in endometriosis has demonstrated that coexistence does not necessarily imply causation. Therefore, a reconsideration of the literature is required to clarify the pathophysiology of deep dyspareunia. Aims: To review the pathophysiology of deep dyspareunia, and to propose future research priorities. Methods: A narrative review after appraisal of published frameworks and literature search with the terms (dyspareunia AND endometriosis), (dyspareunia AND deep), (dyspareunia AND (pathophysiology OR etiology)). Main Outcome Variable: Deep dyspareunia (present/absent or along a pain severity scale). Results: The narrative review demonstrates potential etiologies for deep dyspareunia, including gynecologic-, urologic-, gastrointestinal-, nervous system-, psychological-, and musculoskeletal system-related disorders. These etiologies can be classified according to anatomic mechanism, such as contact with a tender pouch of Douglas, uterus-cervix, bladder, or pelvic floor, with deep penetration. Etiologies of deep dyspareunia can also be stratified into 4 categories, as previously proposed for endometriosis specifically, to personalize management: type I (primarily gynecologic), type II (nongynecologic comorbid conditions), type III (central sensitization and genito-pelvic pain/penetration disorder), and type IV (mixed). We also identified gaps in the literature, such as lack of a validated patient-reported questionnaire or an objective measurement tool for deep dyspareunia and clinical trials not powered for sexual outcomes. Conclusion: We propose the following research priorities for deep dyspareunia: deep dyspareunia measurement tools, inclusion of the population avoiding intercourse due to deep dyspareunia, nongynecologic conditions in the generation of deep dyspareunia, exploration of sociocultural factors, clinical trials with adequate power for deep dyspareunia outcomes, partner variables, female sexual response, pathways between psychological factors and deep dyspareunia, and personalized approaches to deep dyspareunia.